The Success of Nursing Team Cooperation in Nursing Care during Pandemic: A Scoping Review - Lilis Widianah; Heni Dwi Windarwati; Tita Hariyanti; Salizar Binti Mohamed Ludin (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Introduction: The nursing care success was depended on teamwork quality and The pandemic situation could affect the increase of nurse workload in performing nursing intervention. Objective: Aimed to identify the factors that could affect nursing team cooperation success in performing nursing care. Method: The scoping review research was conducted through article identification from four databases such as ScienceDirect, ProQuest, EBSCO, and PubMed in 2019-2021 according to PRISMA-ScR. Search article by using these following keyword combinations: “teamwork OR nursing work OR partnership OR nursing team AND nursing care AND pandemic of COVID-19” to collect related articles. Results: Based on the result of 815 scientific article analysis, about 15 full text articles were in accordance with inclusion criteria for the research review. The internal factors which affected teamwork success in nursing care were consisted of human resource, physical condition, and psychological aspect. Meanwhile, the external factors were consisted of communication, work environment, workload, policy, and documentation. Conclusions: The internal and external factors could be used as a base to identify positive and negative aspects that might affect the success of nursing team performance in carrying out nursing care. Abstrak: Latar Belakang: Keberhasilan asuhan keperawatan tergantung pada kualitas kerjasama tim dan situasi pandemi dapat mempengaruhi peningkatan beban kerja perawat dalam melakukan intervensi keperawatan. Tujuan: Untuk mengetahui faktor-faktor yang dapat mempengaruhi keberhasilan kerjasama tim keperawatan dalam melakukan asuhan keperawatan. Metode: Penelitian scoping review ini disusun dengan mengidentifikasi artikel dari empat database seperti ScienceDirect, ProQuest, EBSCO, dan PubMed tahun 2019-2021 menurut PRISMA-ScR. Pencarian artikel dengan menggunakan kombinasi kata kunci sebagai berikut: “teamwork OR nursing work OR partnership OR nursing team AND nursing care AND pandemic of COVID-19” untuk mengumpulkan artikel yangs esuai.  Hasil: Berdasarkan hasil analisis 815 artikel ilmiah terdapat 15 artikel teks lengkap yang memenuhi kriteria inklusi untuk digunakan dalam tinjauan penelitian. Faktor internal yang mempengaruhi keberhasilan kerja sama tim dalam melakukan asuhan keperawatan terdiri dari sumber daya manusia, kondisi fisik, dan aspek psikologis. Sedangkan faktor eksternal terdiri dari komunikasi, lingkungan kerja, beban kerja, kebijakan, dan dokumentasi. Kesimpulan: Faktor internal dan eksternal dapat digunakan sebagai dasar untuk mengidentifikasi aspek positif dan negatif yang dapat mempengaruhi keberhasilan kinerja tim keperawatan dalam melaksanakan asuhan keperawatan.